2018
DOI: 10.1029/2017gc007361
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Physicochemical Conditions of Evaporite Deposition by Stable Magnesium Isotopes: A Case Study of Late Permian Langbeinites

Abstract: Magnesium isotopic compositions of evaporite deposits may record information concerning brine evolution during deposition. We report Mg isotopic values (δ26MgDSM3) measured from an evaporite deposit of langbeinite (K2Mg2(SO4)3) found in the Permian Salado Formation. We used these data to model Mg isotope fractionation between langbeinite and its parent brine. In addition, both measured and theoretical results are used to estimate precipitation temperature and interpret depositional environment. The Salado lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 92 publications
(214 reference statements)
0
2
0
Order By: Relevance
“…Hydrocarbons produced from the Michigan Basin are generally sourced from the Antrim or the Utica Shale, while basinal brines are thought to be derived from the evaporation of Paleozoic seawater, dissolution of evaporites (which could easily influence Mg concentrations in a developing brine, e.g., Feng et al (2018)), and general water-rock interactions (Wilson & Long, 1993;Hanor & McIntosh, 2006;Swezey, 2002;McIntosh et al, 2011). The Green River basin produces hydrocarbons from mostly Cretaceous formations (Toner et al, 2018) and was thought to have developed under a playa-lake model, which may drive the Mg distinction observed here, as calcite precipitation during playa-lake formation drives Mg/Ca ratios in the developing brine (Eugster & Surdam, 1973).…”
Section: Data Quality and Model Resultsmentioning
confidence: 99%
“…Hydrocarbons produced from the Michigan Basin are generally sourced from the Antrim or the Utica Shale, while basinal brines are thought to be derived from the evaporation of Paleozoic seawater, dissolution of evaporites (which could easily influence Mg concentrations in a developing brine, e.g., Feng et al (2018)), and general water-rock interactions (Wilson & Long, 1993;Hanor & McIntosh, 2006;Swezey, 2002;McIntosh et al, 2011). The Green River basin produces hydrocarbons from mostly Cretaceous formations (Toner et al, 2018) and was thought to have developed under a playa-lake model, which may drive the Mg distinction observed here, as calcite precipitation during playa-lake formation drives Mg/Ca ratios in the developing brine (Eugster & Surdam, 1973).…”
Section: Data Quality and Model Resultsmentioning
confidence: 99%
“…However, as detailed above, epsomite is only one mineral out of the five Mg-minerals that precipitate along the course of evaporation of modern seawater (fractional path; e.g., Eugster et al, 1980;Shalev et al, 2018b). Using quantum chemical density functional theory, Feng et al (2018) calculated the equilibrium isotope fractionation between langbeinite, K 2 Mg 2 (SO 4 ) 3 , and its precipitating solution, to be +0.4‰ at 25°C. Based on this value and the d 26 Mg of three Permian langbeinite samples (-3.9‰) they suggested that the d 26 Mg value of the Permian parent brine was extremely 26 Mg-depleted, ca.…”
Section: Introductionmentioning
confidence: 99%